Whole-genome sequence of the filamentous diazotrophic cyanobacterium Tolypothrix sp. PCC 7712 and its comparison with non-diazotrophic Tolypothrix sp. PCC 7601 - Bozan, Mahir; Popp, Denny; Kallies, Rene; da Rocha, Ulisses Nunes; Klähn, Stephan; Bühler, Katja (Frontiers in Microbiology, 2022)
Cyanobacteria are highly promising microorganisms in forthcoming biotechnologies. Besides the systematic development of molecular tools for genetic engineering, the design of chassis strains and novel reactor concepts are in focus. The latter includes capillary biofilm reactors (CBR), which offer a high surface area-to-volume ratio and very high cell densities. In this context, Tolypothrix sp. PCC 7712 was found to be highly suited for this reactor system due to maximal surface coverage, extraordinarily strong biofilm attachment, and high biomass formation. Here, we provide the genome sequence of Tolypothrix sp. PCC 7712 to potentially allow targeted strain engineering. Surprisingly, it was almost identical to an available incomplete genome draft of Tolypothrix sp. PCC 7601. Thus, we completely sequenced this strain as well and compared it in detail to strain PCC 7712. BlastN analysis showed 257 and 80 unique coding sequences for PCC 7601 and PCC 7712 genomes, respectively. Clustering genomes based on average nucleotide identity (ANI) showing 99.98% similarity indicated no distance between two strains in contrast to high differences compared to 21 other cyanobacterial genomes. Despite these high similarities, both strains differ in the ability to fix atmospheric nitrogen and show specific sequence variations, which are discussed in the paper.